Prevalence of Musculoskeletal Pain and its Correlation with Quality of Life Among Healthcare College Staff Members: A QuestionnaireBased Cross-Sectional Study (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2026)
Background: Musculoskeletal pain (MSP) is a leading occupational health problem worldwide and a major contributor to disability and reduced work productivity. Academic staff in healthcare institutions are at increased risk due to prolonged teaching hours, static postures, and suboptimal ergonomics.Objective: To determine the prevalence of MSP and its correlation with quality of life (QoL) among healthcare college staff members.Design: Questionnaire-based cross-sectional study.Methods: A questionnaire-based cross-sectional study was conducted among 66 healthcare college staff members in Bengaluru, Karnataka. MSP was assessed using the Nordic Musculoskeletal Questionnaire and QoL using the SF-36 Health Survey. Descriptive statistics, independent t-tests, and Spearman correlation were applied using SPSS v27.Results: The prevalence of MSP was high, with the lower back (80.3%), neck (69.7%), and shoulders (39.4%) most affected. Low back pain was significantly associated with lower PCS (p=0.002) and MCS (p=0.006) scores. Shoulder pain was significantly correlated with MCS (p=0.016). PCS scores were significantly associated with BMI, daily computer use, and teaching hours, while MCS was associated with designation. A moderate positive correlation was observed between PCS and MCS (r=0.474, p
Keywords: Musculoskeletal Pain; Quality of Life; Occupational Health